HCN channels segregate stimulation‐evoked movement responses in neocortex and allow for coordinated forelimb movements in rodents - Boychuk, Jeffery A. (J Physiol, 2016)
KEY POINTS: The present study tested whether HCN channels contribute to the organization of motor cortex and to skilled motor behaviour during a forelimb reaching task. Experimental reductions in HCN channel signalling increase the representation of complex multiple forelimb movements in motor cortex as assessed by intracortical microstimulation. Global HCN1(KO) mice exhibit reduced reaching accuracy and atypical movements during a single‐pellet reaching task relative to wild‐type controls. Acute pharmacological inhibition of HCN channels in forelimb motor cortex decreases reaching accuracy and increases atypical movements during forelimb reaching. ABSTRACT: The mechanisms by which distinct movements of a forelimb are generated from the same area of motor cortex have remained elusive. Here we examined a role for HCN channels, given their ability to alter synaptic integration, in the expression of forelimb movement responses during intracortical microstimulation (ICMS) and movements of the forelimb on a skilled reaching task. We used short‐duration high‐resolution ICMS to evoke forelimb movements following pharmacological (ZD7288), experimental (electrically induced cortical seizures) or genetic approaches that we confirmed with whole‐cell patch clamp to substantially reduce I (h) current. We observed significant increases in the number of multiple movement responses evoked at single sites in motor maps to all three experimental manipulations in rats or mice. Global HCN1 knockout mice were less successful and exhibited atypical movements on a skilled‐motor learning task relative to wild‐type controls. Furthermore, in reaching‐proficient rats, reaching accuracy was reduced and forelimb movements were altered during infusion of ZD7288 within motor cortex. Thus, HCN channels play a critical role in the separation of overlapping movement responses and allow for successful reaching behaviours. These data provide a novel mechanism for the encoding of multiple movement responses within shared networks of motor cortex. This mechanism supports a viewpoint of primary motor cortex as a site of dynamic integration for behavioural output.